Utilization of Tsunami Modeling in Determining Temporary Evacuation Spots on the Labuan Coast - Sariwardoyo, Awanda Muthia; Arifin, Wildan Aprizal; Larasati, Wenny Ananda; Nurokhim, Arif; Sriyanto, Sesar Prabu Dwi (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Indonesia is one of the countries with more water surface than land and, in addition, its territory is located between three plates: the Indo-Australian, the Eurasian and the Pacific. This makes Indonesia a country with high volcanic and seismic activity. The abundant news related to mega-earthquakes has made many Indonesians wary of these phenomena. The Sunda Strait is one of the places where megathrustings are expected to occur, and Banten, being a province located in the ocean of the Sunda Strait, makes the level of vigilance high. The modeling process related to tsunami is a representation that can visualize if a large earthquake occurs and causes a tsunami, especially in the coastal area of Labuan subdistrict. The objective of this research is to determine the temporary evacuation spots in tsunami affected areas using tsunami modeling performed with COMCOT (Cornell Multi-grid Coupled Tsunami Grid). The modeling results obtained a wave height to the shoreline of 15 meters with a period to the shoreline of 60 minutes. Twelve temporary evacuation spots (TES) were determined in this study, 9 of the 12 spots become safe TES because the point has a higher ground level and is out of the inundation range.